Change in posttraumatic stress disorder–related thoughts during treatment: Do thoughts drive change when pills are involved?. Issue 2 (31st December 2021) - Rauch, Sheila A.M.; Kim, H. Myra; Venners, Margaret R.; Porter, Katherine E.; Norman, Sonya B.; Simon, Naomi M.; Rothbaum, Barbara O.; Tuerk, Peter W.; Acierno, Ronald E.; Bui, Eric; Powell, Corey; Smith, Erin R.; et al.
Abstract: Posttraumatic negative thoughts about one's self and the world are related to posttraumatic stress disorder (PTSD) symptom severity and change in cognitive behavioral treatment (CBT), but little is known about this association when CBT is delivered with medication. The current study presents a planned comparison of changes in negative posttraumatic thoughts during (a) prolonged exposure (PE) plus pill placebo (PE+PLB), (b) sertraline plus enhanced medication management (SERT+EMM), and (c) PE plus sertraline (PE+SERT) as part of a randomized clinical trial in a sample of 176 veterans. Lagged regression modeling revealed that change in posttraumatic negative thoughts was associated with PTSD symptom change in the conditions in which participants received sertraline, d s = 0.14–0.25, p s = 0.04–.001). However, contrary to previous research, the models that started with symptom change were also statistically significant, d  = 0.23, p  < .001, for the lagged effect of symptoms on negative thoughts about self in the SERT+EMM condition, indicating a bidirectional association between such thoughts and PTSD symptoms. In the PE+PLB condition, no significant association between posttraumatic thoughts and PTSD symptoms emerged in either direction. These results suggest that the previously demonstrated role of change in posttraumatic thoughts leading to PTSD symptom reduction in PE may be altered when combined with pill administration, either active or placebo.